The Development of Canva-Based Animated Videos to Improve Critical Thinking Skills of Elementary/Islamic Elementary School Students in Science Classes on Human Digestive System Materials - Hilmiyati, Fitri; Nafsi, Agni Gina; Sabri, Sabri (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The background of this research is the lack of interactive learning media that can stimulate critical thinking learning, and the difficulty of teachers in developing IT-based learning media. The research objective was to determine the development and feasibility procedures of Canva-based animated video media to improve critical thinking skills in science lessons. The method used in this research is Research and Development (R&D) with the ADDIE research model, which consists of 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Based on the steps above, the researchers produced a product in the form of an animated video based on Canva in natural science lessons on the human digestive system. From the data obtained after the feasibility test results were validated by media experts and material experts with an overall validator score of 93.74% in the